Study of B0 -> D*- pi+ pi- pi+ and B0 -> D*- K+ pi- pi+ decays - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2013)
Using proton-proton collision data collected by the LHCb experiment at sqrt(s) = 7 TeV, corresponding to an integrated luminosity of 1.0 fb^{-1}, the ratio of branching fractions of the B0 -> D*- pi+ pi- pi+ decay relative to the B0 -> D*- pi+ decay is measured to be B(B0 -> D*- pi+ pi- pi+) / B(B0 -> D*- pi+) = 2.64 ± 0.04 (stat.) ± 0.13 (syst.). The Cabibbo-suppressed decay B0 -> D*- K+ pi- pi+ is observed for the first time and the measured ratio of branching fractions is B(B0 -> D*- K+ pi- pi+) / B(B0 -> D*- pi+ pi- pi+) = (6.47 ± 0.37 (stat.) ± 0.35 (syst.)) x 10^{-2}. A search for orbital excitations of charm mesons contributing to the B0 -> D*- pi+ pi- pi+ final state is also performed, and the first observation of the B0 -> Dbar_{1}(2420)^0 pi+ pi- decay is reported with the ratio of branching fractions B(B0 -> (Dbar_{1}(2420)^0 -> D*- pi+) pi- pi+) / B(B0 -> D*- pi+ pi- pi+) = (2.04 ± 0.42 (stat.) ± 0.22 (syst.)) x 10^{-2}, where the numerator represents a product of the branching fractions B(B0 -> Dbar_{1}(2420)^0 pi- pi+) and B(Dbar_{1}(2420)^0 -> D*- pi+).